2014
DOI: 10.1002/anie.201308254
|View full text |Cite
|
Sign up to set email alerts
|

SF and SC Activation of SF6 and SF5 Derivatives at Rhodium: Conversion of SF6 into H2S

Abstract: The degradation of SF6 and SF5 organyls by S-F and S-C bond-activation reactions at [{Rh(μ-H)(dippp)}2] under mild conditions is reported. Fluorido and thiolato species were identified as products or intermediates, and were characterized by X-ray diffraction analysis and multinuclear NMR spectroscopy. An unprecedented cyclic process for the conversion of the potent greenhouse gas SF6 into H2S was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 75 publications
0
35
0
1
Order By: Relevance
“…There is no indication of the pres- ence of a non-classical structure (i.e., an interaction between a silyl and a hydrido ligand). [37] Note that often bis(silyl) complexes show a mutual cis orientation of the SiR 3 ligands, [36,38] but trans arrangements are also known [31,35] . [11] Such a degradation reaction can be avoided by the use of the highly fluorinated β-diketimine 17.…”
Section: Thementioning
confidence: 99%
“…There is no indication of the pres- ence of a non-classical structure (i.e., an interaction between a silyl and a hydrido ligand). [37] Note that often bis(silyl) complexes show a mutual cis orientation of the SiR 3 ligands, [36,38] but trans arrangements are also known [31,35] . [11] Such a degradation reaction can be avoided by the use of the highly fluorinated β-diketimine 17.…”
Section: Thementioning
confidence: 99%
“…[19][20][21] In most of the cases the fate of the sulfur atom remained unclear. [22] In the presence of HSiEt 3 the reaction led selectively to fluorosilane,H 2 ,and the thiolato-bridged complex [Rh 2 (m-H)(m-SSiEt 3 )(dippp) 2 ], which was obtained exclusively as the only sulfur-containing product. [22] In the presence of HSiEt 3 the reaction led selectively to fluorosilane,H 2 ,and the thiolato-bridged complex [Rh 2 (m-H)(m-SSiEt 3 )(dippp) 2 ], which was obtained exclusively as the only sulfur-containing product.…”
mentioning
confidence: 99%
“…Note that in our previous study on employing binuclear rhodium compounds for SF 6 activation [22] the cleavage of the sulfur-rhodium bonds turned out to be amajor restriction to accomplish ac atalytic pathway.W ea ttributed this to the bridging sulfur atom between two rhodium centers at [Rh 2 (m-H)(m-SSiEt 3 )(dippp) 2 ], which makes the rhodium-sulfur interaction very stable.W et herefore assume that reactions at cationic rhodium centers,s uch as in 3 or 6,d on ot lead to binuclear sulfide species,w hich might hamper ac atalytic turnover. Indeed, further studies revealed that the ionic complex 6 is also able to catalyze the degradation of SF 6 with HSiEt 3 and PEt 3 .T he reaction proceeded also selectively to yield H 2 as well as F 2 PEt 3 ,F SiEt 3 ,a nd SPEt 3 as the only SF 6 decomposition products.Byusing 2.5 mol %of6,the TON for the SPEt 3 formation after 16 ha t8 0 8 8Cw as 12 (Table 1, entry 22), which is identical to the reaction with 1 as catalyst precursor (Table 1, entry 7).…”
mentioning
confidence: 99%
“…They described the reaction between sulfur hexafluoride and hydrogen sulfide to sulfur and hydrogen fluoride. Furthermore, reactions with elemental sodium at 200 • C and several catalytic activations with nickel-or rhodium-complexes of SF 6 have been published [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its excellent electric characteristics and high chemical stability, it is used as a dielectric medium in high-voltage circuit breakers, transformers, capacitors and many more industrial applications [3]. Since the search for a replacement material that is less harmful to the environment or that is easier to dispose of has not yet been successful, the decomposition of sulfur hexafluoride remains a current field of research [4][5][6].…”
Section: Introductionmentioning
confidence: 99%